Major pathologic response on biopsy (MPRbx) in patients with advanced melanoma treated with anti-PD-1: evidence for an early, on-therapy biomarker of response. (23rd January 2019) - Stein, J E; Soni, A; Danilova, L; Cottrell, T R; Gajewski, T F; Hodi, F S; Bhatia, S; Urba, W J; Sharfman, W H; Wind-Rotolo, M; Edwards, R; Lipson, E J; et al.
Abstract: Background: With increasing anti-PD-1 therapy use in patients with melanoma and other tumor types, there is interest in developing early on-treatment biomarkers that correlate with long-term patient outcome. An understanding of the pathologic features of immune-mediated tumor regression is key in this endeavor. Materials and methods: Histologic features of immune-related pathologic response (irPR) following anti-PD-1 therapy were identified on hematoxylin and eosin (H&E)-stained slides in a discovery cohort of pre- and on-treatment specimens from n = 16 patients with advanced melanoma. These features were used to generate an irPR score [from 0 = no irPR features to 3 = major pathologic response on biopsy (MPRbx, ≤10% residual viable tumor)]. This scoring system was then tested for an association with objective response by RECIST1.1 and overall survival in a prospectively collected validation cohort of pre- and on-treatment biopsies ( n = 51 on-treatment at 4-week timepoint) from melanoma patients enrolled on the nivolumab monotherapy arm of CA209-038 (NCT01621490). Results: Specimens from responders in the discovery cohort had features of immune-activation (moderate–high TIL densities, plasma cells) and wound-healing/tissue repair (neovascularization, proliferative fibrosis) compared to nonresponders, ( P ≤ 0.021, for each feature). In the validation cohort, increasing irPR score associated with objective response ( P = 0.009) and MPRbx associated with increased overall survival ( n = 51; HR 0.13; 95%CI, 0.054–0.31, P = 0.015). Neither tumoral necrosis nor pretreatment histologic features were associated with response. Eight of 16 (50%) of patients with stable disease showed irPR features, two of which were MPRbx, indicating a disconnect between pathologic and radiographic features at the 4-week on-therapy timepoint for some patients. Conclusions: Features of immune-mediated tumor regression on routine H&E-stained biopsy slides from patients with advanced melanoma correlate with objective response to anti-PD-1 and overall survival. An on-therapy biopsy may be particularly clinically useful for informing treatment decisions in patients with radiographic stable disease. This approach is inexpensive, straightforward, and widely available.